In vitro biocompatibility analysis of protein-resistant amphiphilic polysulfobetaines as coatings for surgical implants in contact with complex body fluids - Karthäuser, Jana F.; Gruhn, Dierk; Martínez Guajardo, Alejandro; Kopecz, Regina; Babel, Nina; Stervbo, Ulrik; Laschewsky, André; Viebahn, Richard; Salber, Jochen; Rosenhahn, Axel (Frontiers in Bioengineering and Biotechnology, 2024)
The fouling resistance of zwitterionic coatings is conventionally explained by the strong hydrophilicity of such polymers. Here, the in vitro biocompatibility of a set of systematically varied amphiphilic, zwitterionic copolymers is investigated. Photocrosslinkable, amphiphilic copolymers containing hydrophilic sulfobetaine methacrylate (SPe) and butyl methacrylate (BMA) were systematically synthesized in different ratios (50:50, 70:30, and 90:10) with a fixed content of photo-crosslinker by free radical copolymerization. The copolymers were spincoated onto substrates and subsequently photocured by UV irradiation. Pure pBMA and pSPe as well as the prepared amphiphilic copolymers showed BMA content-dependent wettability in the dry state, but overall hydrophilic properties a fortiori in aqueous conditions. All polysulfobetaine-containing copolymers showed high resistance against non-specific adsorption (NSA) of proteins, platelet adhesion, thrombocyte activation, and bacterial accumulation. In some cases, the amphiphilic coatings even outperformed the purely hydrophilic pSPe coatings.